Erratum: Gómez-Montoya, N., Drechsler-Santos, E.R., Ferreira-Lopes, V., Tomšovský, M., Urcelay, C. & Robledo, G.L. (2017) New insights on Trametopsis Tomšovský (Polyporales Gäum) based on phylogenetic evidences and morphological analyses of neotropical species. Phytotaxa 311 (2): 155–167. - Gómez-Montoya, Nataly; Drechsler-Santos, Elisandro Ricardo; Ferreira-Lopes, Valéria; Tomšovský, Michal; Urcelay, Carlos; Robledo, Gerardo Lucio (Phytotaxa, 2017)
N/A